2015
DOI: 10.1039/c5cc02581h
|View full text |Cite
|
Sign up to set email alerts
|

Solid lithium electrolytes based on an organic molecular porous solid

Abstract: A new type of solid lithium-ion conducting electrolytes prepared by incorporation of Li(+) ions into a cucurbit[6]uril (CB[6])-based organic molecular porous solid shows high Li(+) ion conductivity (∼10(-4) S cm(-1)) and mobility (transference numbers, tLi(+) = 0.7-0.8). In addition, the solid electrolytes show excellent, thermally stable performance even after several temperature cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Other than proton conduction, Kim and co‐workers also reported a new type of solid lithium‐ion conducting electrolyte by incorporating Li + ions into a 25 ‐based guest‐free COM, which displayed high Li + ion conductivity (about 10 −4 S cm −1 ) and high cationic transference number . Additionally, the solid electrolytes displayed thermally stable even after several temperature cycles.…”
Section: Cb‐based Comsmentioning
confidence: 99%
“…Other than proton conduction, Kim and co‐workers also reported a new type of solid lithium‐ion conducting electrolyte by incorporating Li + ions into a 25 ‐based guest‐free COM, which displayed high Li + ion conductivity (about 10 −4 S cm −1 ) and high cationic transference number . Additionally, the solid electrolytes displayed thermally stable even after several temperature cycles.…”
Section: Cb‐based Comsmentioning
confidence: 99%
“…Recently,S hen et al demonstrated that quasi-solid lithium ion conductors can be fabricated by constructing biomimetici on channels in MOFs. [66] It exhibits an ionic conductivity in the order of 10 À4 Scm À1 and ah igh lithium transferencen umber of 0.7-0.8. Systematic studies reveal that larger pore size and stronger Lewis acidity of OMSs favor the lithium iont ransport in MOF channels.…”
Section: Open-framework-liquid Hssesmentioning
confidence: 99%
“…Organic porousm aterialc ucurbit[6]uril (CB[6]) with ah oneycomb-like structure and1 Dc hannels has been studied as HSSE after incorporation of lithium ions (Figure 7a). [66] It exhibits an ionic conductivity in the order of 10 À4 Scm À1 and ah igh lithium transferencen umber of 0.7-0.8. Zhang and co-workers designed an ew type of COF linked by spiroborates, containing abundant pores and sp 3 hybridized boron anionic centers (Figure 7b).…”
Section: Open-framework-liquid Hssesmentioning
confidence: 99%
“…d) Arrhenius plots of various LPC@MOFs electrolytes and their calculated activation energies for lithium‐ion conduction. e) Arrhenius plots of LPC@MIL‐100‐Al (pink), LPC@MIL‐100‐Fe (dark yellow), and LPC@UiO‐67 (cyan) in comparison with representative 1) ceramic electrolytes (Li 10 GeP 2 S 12 , garnet Li 7 La 3 Zr 2 O 12 , and LiPON Li 3.5 PO 3 N 0.5 ); 2) polymeric electrolytes (LiClO 4 /PEO with TiO 2 additive, LiTFSI‐PC in crosslinked SiO 2 ‐PEO composites, and single ion polymer P(STFSILi)‐PEO‐P(STFSILi)); 3) liquid‐in‐solid lithium‐ion conductors, including liquid electrolyte@mesoporous silica, LiPF 6 ‐EC/DMC/DEC@SiO 2 , LPC@organic porous solids, CB[6]·0.4LiClO 4 ·3.4 PC, Li alkoxide@MOFs, Mg 2 (dobdc)·0.35LiO i Pr·0.25LiBF 4 ·EC·DEC,[16a] Li halide‐PC@MOFs, Li 0.8 [Cu 2 Cl 2 Br 0.8 BTDD]·10(PC), and ionic liquid@MOFs, (EMI 0.8 Li 0.2 )TFSA@ZIF‐67; and 4) liquid electrolyte, 1 m LiClO 4 in PC (LPC).…”
mentioning
confidence: 99%